2010
DOI: 10.1109/tdei.2010.5595554
|View full text |Cite
|
Sign up to set email alerts
|

Short-term breakdown and long-term failure in nanodielectrics: a review

Abstract: Nanodielectrics, which are concentrated in polymer matrix incorporating nanofillers, have received considerable attention due to their potential benefits as dielectrics. In this paper, short-term breakdown and long-term failure properties of nanodielectrics have been reviewed. The characteristics of polymer matrix, types of nanoparticle and its content, and waveforms of the applied voltage are fully evaluated. In order to effectively comment on the published experimental data, a ratio k has been proposed to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
181
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 291 publications
(186 citation statements)
references
References 74 publications
3
181
0
2
Order By: Relevance
“…In another study on electrical treeing [9], tree growth was suppressed, provided the nanocomposite was free of agglomerations, since these can serve as regions of locally high permittivity. Other authors [10] identify good nanoparticle dispersion as being a key prerequisite for enhanced electrical performance of nanocomposites. Over a wide range of material formulations, improved performance was reported for nanocomposites with…”
Section: Introductionmentioning
confidence: 99%
“…In another study on electrical treeing [9], tree growth was suppressed, provided the nanocomposite was free of agglomerations, since these can serve as regions of locally high permittivity. Other authors [10] identify good nanoparticle dispersion as being a key prerequisite for enhanced electrical performance of nanocomposites. Over a wide range of material formulations, improved performance was reported for nanocomposites with…”
Section: Introductionmentioning
confidence: 99%
“…It has also been found that the related electrical performance, surface flashover, and breakdown deteriorate for nanodielectrics with high concentrations. 3,4,8,9 At present, the exact mechanisms of charge transport in nanodielectrics are not detailed, and the observed experiment phenomenon of charge conduction in nanodielectrics with high loading concentrations has never been fully explained.…”
mentioning
confidence: 99%
“…Previous research work has indicated that this new conduction mechanism could 2 Journal of Nanotechnology be associated with the electromechanical compression of the polymer and polarization mode. It is known that the morphology of a polymer can be modified by nanofillers (e.g., nanoparticles, nanowires, and nanolayers), due to the large interface interaction (surface to volume ratio) [9], so that the mechanical, thermal, and electrical properties of the polymer could be affected significantly by the introduction of nanofillers [10,11]. Here, we report evidence for the presence of such solitonlike ultra fast space charge packets in epoxy-based nanocomposites.…”
Section: Introductionmentioning
confidence: 73%